FACTORS INFLUENCING DIGITAL BANKING SERVICE QUALITY: A COMPARATIVE STUDY BETWEEN SBI AND ICICI BANK IN BANGALORE - Singh, Dr. Arti; Rana, Dr. Sarita; M, Sridhar; Agrawal, Dr. Divya Kumar; Khizerulla, Dr. Mohammed (The journal of contemporary issues in business and government, 2022)
Digital banking services in India plays an important role since 5 years as the customers are looking beyond the traditional way of banking. Digital banking Services like Electronic Fund Transfer(NEFT,RTGS,IMPS), UPI, ATM, Cash deposit machine, Mobile Banking Application, Debit Card, Credit Card are growing exponentially since 2017 due to the several initiative by government like incentives for customers and merchants, Demonetization, financial inclusion and for customer and tradersown interest and lastly due to Covid-19. Study conducted in the Bangalore region by using purposive sampling technique. The sample for the study was collected using structured questionnaire with the help of Google form and sample size was 101. Study found that SBI is strong as compared to ICICI with respect to factors such as Efficiency, System availability, Fulfillment, responsiveness, website design. But whereas ICICI is showing positive significance in the case of Privacy and Website design is concerned.